Strong coupling in microcavity structures : principle, design, and practical application - Yu, Xiantong (2020)
When interaction between light and matter is in the strong coupling region, matter has a significant influence on the whole system, with potential to develop low‐power active optical devices. Strong coupling can verify some basic problems of quantum physics, and it is an ideal system to study light–matter interaction, providing an intuitive and accurate demonstration of some pure quantum effects with small mass and easy optical control. Here, the most important advances in strong coupling in recent years are described. Of late, an extensive series of experimental and theoretical findings, and remarkable achievements have been made in this field. Strong coupling between cavities and some new materials such as semiconductors, two‐dimensional (2D) material, and quantum dots (QDs) are the focus of research in this field. Another field that has made outstanding progress is the application of this optical phenomenon, including resonance‐enhanced Raman and infrared spectra, nanolasers, and cavity‐enhanced sensing. Furthermore, the potential in this field arises for future quantum information and quantum optical devices. It is now developing at a very fast rate and can be predicted to have broad prospects for development in the future. Some prospects in terms of design and application are included.